2018
DOI: 10.1088/1361-6463/aaa5c5
|View full text |Cite
|
Sign up to set email alerts
|

An ENG resonator-based microwave sensor for the characterization of aqueous glucose

Abstract: This work proposes a microwave filter with a notched frequency of transmission using an epsilon negative (ENG) unit-cell resonator as a sensor device. The device finds important application for the characterization of life-saving samples such as glucose. The ENG structure consists of two complementary geometries in the shape of ring and horn. The structure efficiently inhibits the incoming RF signal and creates a stopband resonance at 2.074 GHz. The printed circuit board of the layout was realized using FR-4 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 20 publications
0
30
1
Order By: Relevance
“…Finally, the proposed sensor is compared to other published results in References in terms of F r , measurement error, structure type, and the distance between the sample and the sensor as listed in Table . It is found that the proposed sensor shows the minimum measurement error with a single port network and far away from the sample of 100 mm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, the proposed sensor is compared to other published results in References in terms of F r , measurement error, structure type, and the distance between the sample and the sensor as listed in Table . It is found that the proposed sensor shows the minimum measurement error with a single port network and far away from the sample of 100 mm.…”
Section: Resultsmentioning
confidence: 99%
“…A partial ground plane of the monopole antenna is used to provide a constant electric flux for sensing in the far fields and/or near fields of the antenna as seen in Figure . The circuit design of the patch follows the concept of composite right/left‐handed MTM . The LH behavior is attributed to the induced capacitance and inductance effects from the integrated C int to the patch and via to the ground plane, respectively.…”
Section: Hypothesis Of the Sensing Philosophymentioning
confidence: 99%
See 2 more Smart Citations
“…are in use. Recently, microwave planar sensors based on metamaterial units such as split ring resonator (SRR) 26 , complementary split ring resonator (CSRR) 27 , open split ring resonator (OSRR) 28 , complementary electric LC (ELC) resonator 29 and epsilon negative (ENG) unit cell resonator 30 are gaining popularity for glucose sensing due to the enhanced sensitivity, low cost, compactness, and ease of manufacture and measurement.…”
Section: Introductionmentioning
confidence: 99%